SEROPREVALENCE OF NEWCASTLE DISEASE IN DOMESTIC CHICKEN IN TABANAN DISTRICT BALI - Surbakti, Ledi Natalia; Kencana, Gusti Ayu Yuniati; Suartha, I Nyoman (Buletin Veteriner Udayana, 2021)
Newcastle Disease (ND) is one of the poultry diseases that can infect domestic chickens. It is an infectious disease that has a detrimental impact on chicken farmers. ND infection can be acute to chronic, and it can also affect all types of poultry, especially chickens, both broiler and domestic chickens. Tabanan Subdistrict is a location where poultry trade activities are often carried out between regions and/ or provinces, so domestic chickens have the potential to be exposed to ND. This study aims to determine the disease seroprevalence in domestic chickens in Tabanan District, Tabanan Regency, Bali. The sample of this study was serum from chicken’s blood samples that were taken from six villages in Tabanan Sub-district. Samples were taken from villages where each village consisted of three banjars. Banjar is a division of Bali administrative areas, and eight samples of domestic chickens were collected from each sampled banjar. A total sample of 144 serums of non-vaccinated domestic chicken. Serum was tested serologically with hemagglutination (HI) test at the Virology Laboratory of the Faculty of Veterinary Medicine, Udayana University. The results showed that ND seroprevalence in domestic chickens in Tabanan Subdistrict was 3.17%. Positive samples were gathered from Gubug, Bongan, and Wanasari villages with antibody titers ranged from 2 4 to 2 5 . The conclusions of seropositive results showed that domestic chicken in the Tabanan district has currently been infected with the Newcastle Disease virus.